Capacidad acumuladora de la raíz de Paspalum depauperatum L. “manga larga” al plomo y cadmio, en condiciones de laboratorio - Cueva Acuña, Luz Marina (2017)
At present, several investigations on phytoremediation are being carried out, where the aim is to clean ecosystems through the use of wild plants. One of these plants is Paspalum depauperatum L. "long sleeve, which inhabits polluted aquatic environments such as those from mining activity in the province of Otuzco. Therefore the objective of the research was to determine the accumulating capacity of lead and cadmium by the roots of P. depauperatum L. "long sleeve", exposed to concentrations of 0.0; 10.0; 20.0 and 30.0 ppm of lead and 0.0, 1.0, 2.0, 3.0 ppm of cadmium, in laboratory conditions. The plants of P. depauperatum L. "long sleeve" were transferred to the laboratory of Environmental Genotoxicity of the Faculty of Biological Sciences for their adaptation. The experimental design of increasing stimulus was constituted by concentrations of 0.0, 10.0, 20.0 and 30.0 ppm of lead, with one control, three treatments and three repetitions. The same design was applied to the investigation with cadmium using concentrations of 0.0 1.0, 2.0 and 3.0 ppm, with one control, four treatments and three repetitions. The data were subjected to the tests of Anova and Tukey . The root of P. depauperatum L. "long sleeve" accumulated 1,082 ppm of lead in treatment 3 (30ppm) in the second sample, value that increases again in the fourth and fifth sampling. The root of P. depauperatum L. "long sleeve" accumulated 0.09923 ppm of cadmium in the treatment 3 (3ppm) of cadmium, accumulating the accumulation values almost similar in the following days of sampling. The results show that P. depauperatum L. has an accumulating capacity of lead and cadmium.